Segregated ice growth in a suspension of colloidal particles - Aarts, D; Dullens, R; Schollick, J; Style, R; Wettlaufer, J; Curran, A; Velikov, K; Warren, P; Dufresne, E (American Chemical Society, 2017)
We study the freezing of a dispersion of colloidal silica particles in water, focusing on the formation of segregated ice in the form of ice lenses. Local temperature measurements in combination with video microscopy give insight into the rich variety of factors that control ice lens formation. We observe the initiation of the lenses, their growth morphology and their final thickness and spacing, over a range of conditions, in particular the effect of the particle packing and the cooling rate. We find that increasing the particle density drastically reduces the thickness of lenses, but has little effect on the lens spacing. Therefore, the fraction of segregated ice formed reduces. The effect of the cooling rate, which is the product of the temperature gradient and the pulling speed across the temperature gradient, depends on which parameter is varied. A larger temperature gradient causes ice lenses to be initiated more frequently, while a lower pulling speed allows for more time for ice lenses to grow: both increase the fraction of segregated ice. Surprisingly, we find that the growth rate of a lens does not depend on its undercooling. Finally, we have indications of pore ice in front of the warmest ice lens, which has important consequences for the interpretation of the measured trends. Our findings have important consequences for ice segregation occurring in a wide range of situations, ranging from model lab experiments and theories, to geological and industrial processes, like frost heave and frozen food production.